Pre or perioperative period: when is the best time to produce platelet-rich plasma in dogs? - Grazielle Anahy de Sousa Aleixo; Maria Cristina de Oliveira Coelho; Miriam Nogueira Teixeira; Lilian Sabrina Silvestre Andrade; Maria Clara Cunha Paranhos de Oliveira; Flávia Corrêa Maia; Ana Luiza Neves Guimarães Bessa; Joaquim Evêncio-Neto; Emanuela Polimeni Mesquita (Medicina Veterinária, 2022)
When evaluating published studies on the production of platelet-rich plasma (PRP), it is possible to observe that there is no consensus on when blood should be collected and processed. Some perform blood collection before surgery, prior to the administration of drugs, fluids, or any surgical trauma, while others collect blood during the perioperative period. The present objective was to determine the best moment for PRP production based on the platelet count. Blood samples were collected from 20 healthy female dogs at two distinct moments: before surgery, prior to anesthesia and fluid therapy (M0), and later, in the operation room, after administration of the anesthetics and intravenous fluids (M1). To obtain PRP, blood was centrifuged at 1200 rpm for ten minutes, then at 1600 rpm for ten minutes. Results showed that the blood collected at M1 had a 29% decrease in platelet count compared to M0 (highly significant statistical difference). It is recommended that blood collection, which is an essential step for producing platelet-rich plasma, shall be done during the pre-operative period.